Identification of the sites of action for regulatory genes controlling the amdS gene of Aspergillus nidulans. - Hynes, M J (1988)
The amdS gene of Aspergillus nidulans, which encodes an acetamidase enzyme, is positively regulated by the trans-acting genes amdR, facB, amdA, and areA. Sequence changes in several cis-acting mutations in the 5' region of the gene which specifically affect amdS regulation were determined. The amdI9 mutation, which results in increased facB-dependent acetate induction, is due to a single-base change at base pair -210 relative to the start point of translation. The amdI93 mutation, which abolishes amdR-dependent omega-amino acid induction, is a deletion of base pairs -181 to -151. The amdI66 mutation, which causes increased gene activation in strains carrying amdA regulatory gene mutations, is a duplication of base pairs -107 to -90. Transformation of A. nidulans can generate transformants containing multiple integrated copies of plasmid sequences. When these plasmids carry a potential binding site for a regulatory gene product, growth on substrates whose catabolism requires genes activated by that regulatory gene can be reduced, apparently because of titration of the regulatory gene product. Introduction of 5' amdS sequences via cotransformation into strains of various genotypes was used to localize sequences apparently involved in binding of the products of the amdR, amdA, and facB genes. The position of these sequences is in agreement with the positions of the specific cis-acting mutations. Consistent with these results, a transformant of A. nidulans derived from a plasmid deleted for sequences upstream from -111 was found to have lost amdR- and facB-mediated control but was still regulated by the amdA gene. In addition, amdS expression in this transformant was still dependent on the areA gene.